Rural Tourism and the Sustainable Development Goals. A Study of the Variables That Most Influence the Behavior of the Tourist - López-Sanz, José María; Penelas-Leguía, Azucena; Gutiérrez-Rodríguez, Pablo; Cuesta-Valiño, Pedro (Frontiers in Psychology, 2021)
Tourism is an activity that contributes directly and indirectly to the development of rural areas. But this development needs to be sustainable. To do this, appropriate policies that positively influence these areas from an economic, social and cultural point of view must be implemented. All this in accordance with the Sustainable Development Goals. This study will analyze the contribution of rural tourism to develop and implement policies to promote sustainable tourism that creates jobs and promotes local culture and products. The variables that most influence the tourist behavior, motivation, the destination image, and the satisfaction obtained by the tourist will be analyzed. After an exhaustive review of the literature, an empirical investigation was carried out with 1,658 valid surveys among rural tourists in Soria, a Spanish province with one of the highest levels of depopulation. A structural equation model was drawn up to discover the relationships between the variables. The results demonstrated the importance of the motivation in the formation of the destination image, as well as satisfaction with the trip. In the same way, we will verify which component of the image of the destination (affective or cognitive) has the most influence on their formation, and how the image of the destination, like motivation, influences tourist satisfaction. The proposed model could be used in many studies that analyze the different variables that influence consumer behavior since its reliability and predictive capacity have been proven. The results of the study can also be used by the authorities to design or modify the most appropriate strategies that influence rural tourism, specially promoting the destination image as a variable that positively influences tourist satisfaction.